Location tracking using UWB and IMU - Tan, Tian Fu (Nanyang Technological University, 2022)
Indoor localization, in general, has been an important topic in recent years. Since the covid pandemic, the technology shifting towards automation has never been higher. With the lack of employment due to restrictions and the complexity of what automation is required, Indoor tracking has become an even more relevant technology. The Ultra-Wideband technology is one of the rising technologies that can be a solution due to its renowned accuracy. As Ultra-Wideband has a low update rate, past research combines Inertial Measurement Unit (IMU) with Ultra-Wideband to alleviate the high latency. The Extended Kalman Filter algorithm is a popular fusion algorithm that has been used for many years. However, extended usage of IMU will result in a cumulative error of both accelerometer and gyroscope. The project focus on tackling the downside of IMU and UWB through the use of filters to determine the practicability of the system.